2019
DOI: 10.1002/mrd.23141
|View full text |Cite
|
Sign up to set email alerts
|

Molecular effects on spermatozoa of Mytilus galloprovincialisexposed to hyposaline conditions

Abstract: Salinity represents a critical environmental and an ecological factor in the reproduction of marine species. As global climate changes and anthropogenic factors affect salinity, in this study, we have analyzed the responses of Mytilus galloprovincialis spermatozoa to hyposaline stress. We exposed mussels, in laboratory tanks, for 24 hr at 18°C to control (35.9 psu) and three hyposaline (17.1, 22.6, and 26.2 psu) conditions, and evaluated the expression of sperm hsp70 and protamine‐like proteins genes. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…Hg poisoning in humans manifests as neurological, kidney, immune, and respiratory disorders, and is especially toxic in pregnant women [26,27,28,29,30]. Evidence from human and animal studies suggests that mercury also affects reproductive function [31], as do other heavy metals, such as copper [32,33,34] and cadmium [35]. Moreover, high levels of Hg may induce or exacerbate cardiovascular diseases [36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Hg poisoning in humans manifests as neurological, kidney, immune, and respiratory disorders, and is especially toxic in pregnant women [26,27,28,29,30]. Evidence from human and animal studies suggests that mercury also affects reproductive function [31], as do other heavy metals, such as copper [32,33,34] and cadmium [35]. Moreover, high levels of Hg may induce or exacerbate cardiovascular diseases [36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…We studied, by electrophoretic mobility shift assays (EMSA), the differences in the ability to bind the DNA of the SNBP samples belonging to the control 1 subjects and of the father and son. In particular, we evaluated the proteins/DNA ratio required for obtain DNA saturation, detectable by the formation of a high-molecular weight DNA band, close to the well, in electrophoretic pattern [ 22 ]. All the analyzed SNBP samples interacted with DNA in the typical “all or nothing” DNA binding mode of SNBP in agreement with data previously reported for SNBP [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the mechanism of gamete tolerance to low salt is complex, which may require further research at the molecular level. For example, previous studies have shown that the expression of hsp70 and protein‐like protein genes in sperm is closely related to its response to hyposaline conditions (Lettieri, Maione, et al, 2019). In addition, external fertilizers like oysters can form their own gamete plasticity to adapt to the specific environmental stress of their habitat (Jensen et al, 2014; Lettieri, Maione, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity, as one of the basic indicators of water environment, usually varies with climate changes or human activities, thus affecting the survival of aquatic animals (Kinne, 1964; Lettieri et al, 2019; McNeil & Sasse, 2016). As an important member of aquatic animals, bivalves are affected by salinity in many aspects (Hosoi et al, 2010; Lettieri, Maione, et al, 2019; Madrones‐Ladja, 2002; Taylor et al, 2004; Verween et al, 2007). Oyster is a typical euryhaline bivalve (Xu et al, 2011), and the researches on the effects of salinity on oysters are attracting attention, which mainly focus on gamete quality (Qin et al, 2018), embryonic development (Dos Santos & Nascimento, 1985), fertilization and hatching (Han & Li, 2018), larval growth and survival (Kinne, 1964; Nell & Holliday, 1988), and growth and survival of juvenile (Rybovich, Peyre, Hall, & Peyre, 2016).…”
Section: Introductionmentioning
confidence: 99%